The relationship between diet and other elements of lifestyle and the health status of adult high school students - Koziarska-Rościszewska, Małgorzata; Wiśniewska, Katarzyna (Family Medicine & Primary Care Review, 2017)
Background . Obesity is one of the main causes of “civilization-related” diseases (diabetes mellitus, hypertension, atherosclerosis). Poor dietary habits can influence health even in teenagers. Objectives . The aim of the study was to analyze the relationship between the lifestyle and health of adult high school students (18–20 years old) from Lodz. Material and methods . A group of 106 high school students in Lodz (76 women – 71.7% and 30 men – 28.3%) were enrolled. A questionnaire concerning lifestyle and selected diseases was completed. Anthropometric measurements and physical examination were carried out. BMI and WHR were calculated. In addition, in 35 volunteers out of the respondents blood tests (lipids, glycemia) were done. Results . BMI was ≥ 25 kg/m2 among 19 students (18%). Abnormal waist circumference was observed in 8 (8%) patients, 1 person had abnormal WHR (0.9%). Elevated systolic and/or diastolic blood pressure was observed in 4 students (4%). Elevated total cholesterol was found in 4 respondents (4%), hyperglycemia in the case of 1 person (0.9%). 73 participants (68.9%) attended physical education classes; 62 (58.5%) of them were physically active in their leisure-time. Conclusions . In the examined group of adult high school students cardiovascular risk factors (excessive body weight, dyslipidemia, hypertension) were observed. Improper dietary habits affect the health status in teenagers. The physical activity of the examined young people seems satisfactory. Most of the high school students participate in physical training at school and spend their leisure-time actively. Preventive methods in young people should include proper diet and the promotion of an active lifestyle.